A construção de conhecimento em dispositivos midiáticos: investigação em escolas públicas - Rodrigues, Lylian Caroline Maciel (Universidade do Vale do Rio do Sinos, 2007)
We search the relations between the fields of communication and education in a perspective of mediatic processes. For this, first, we contextualize the subject, grouping the contributions from the communication academic field developed about this interface. At a second moment, we search for theoretical formularization that give support to our axle of problem and that can be briefed in the following question: how the knowledge is produced by media, considering its own place and not in school institution, which is the basic space for learning in society? To operate the relations between these fields, we mobilize the concept of devices, on a triadic perspective - interaction, language and technology. This angle is articulated with other theoretical contributions such as the concepts of belief, habitus, reproduction, distinction, agenda setting and protagonism. The theoretical construct produced in a descending and ascending dialectic process (or, between deductive and inductive processes, with diverse levels of
Keywords: escola; influência; internet; meio; mídia; processo midiático; rádio; televisão; educação; interface; media device; media process; Ciências Sociais Aplicadas